The Impact of Biologic Treatment on PD-1/PD-L1 Pathway Disturbances in Psoriasis - Adamczyk, Michał; Bartosińska, Joanna; Raczkiewicz, Dorota; Michalak-Stoma, Anna; Krasowska, Dorota (Journal of clinical medicine, 2023)
The programmed death-1 (PD-1) receptor plays a major physiological role in the maintenance of immune tolerance and, by interaction with its ligands (PD-L1 and PD-L2), prevents the development of multiple immune-mediated diseases. There is growing evidence of the PD-1/PD-L1 pathway playing an important role in the pathogenesis of psoriasis. In total, 84 subjects with psoriasis were included in this study, together with 29 healthy subjects as a control group. Twenty-eight of the psoriatic patients were treated with biologic therapy (TNF-alpha, interleukin (IL)-12/23, or IL-17 inhibitors). The amounts of PD-1- and PD-L1-positive T-cells in peripheral blood were evaluated using flow cytometry. Significantly lower levels of peripheral blood mononuclear cells (PBMCs) with the expression of PD-1 and PD-L1 were found in psoriatic patients compared to healthy individuals, i.e., CD3/PD-1-, CD3/PD-L1-, CD4/PD-1-, CD4/PD-L1-, CD8/PD-L1-, CD19/PD-1-, and CD19/PD-L1-positive cells. Biologic treatment resulted in the elevation of CD3/PD-L1- and CD8/PD-L1- and a decrease in CD8/PD-1-positive PBMCs. Our results confirm previous observations of the PD-1/PD-L1 pathway being disrupted in psoriasis, and that these disturbances may play an important role in development of the disease. Biologic drugs may reverse several abnormalities observed within this pathway, which may explain their excellent efficacy in the treatment of psoriasis. Further research should be conducted to fully explain the results obtained.